USING THE FLIPPED CLASSROOM MODEL TO ENHANCE ENGLISH SPEAKING SKILLS THROUGH DIGITAL STORYTELLING - Laeli Nuriyah (Jurnal Visi Ilmu Pendidikan, 2023)
The goal of this study is to increase the English language proficiency of 12th grade students through digital storytelling activities based on the Flipped Classroom Model. Students in Al Farhan High School's 12th grade participated in this study. An example of action research can be found here. FCM is used as a framework for teaching English. Students' English speaking abilities will be honed through the use of digital storytelling. Digital fiction's moral message is the topic of this investigation. Students use internet-sourced content in the digital narrative activity to build fictional scenarios. The researcher then received the document over Telegram. After acquiring data, the screenplay material was memorized and then turned into a digital video story. ' Students are introduced to fictional texts and grammatical ideas prior to partaking in digital storytelling activities. Then, a hypothetical situation is provided to reinforce the newly learned information. FCM's use of digital storytelling to educate and learn English as a second language ultimately improves students' speaking abilities.Keywords: Flipped Classroom Model, Digital Storytelling, Speaking Skills. AbstrakPenelitian ini bertujuan untuk meningkatkan kemampuan bahasa Inggris siswa kelas 12 melalui kegiatan digital storytelling berbasis Flipped Classroom Model. Siswa kelas 12 SMA Al Farhan berpartisipasi dalam penelitian ini. Contoh penelitian tindakan dapat ditemukan di sini. FCM digunakan sebagai kerangka kerja untuk mengajar bahasa Inggris. Kemampuan berbicara bahasa Inggris siswa akan diasah melalui penggunaan digital storytelling. Pesan moral fiksi digital menjadi topik investigasi ini. Siswa menggunakan konten yang bersumber dari internet dalam aktivitas naratif digital untuk membangun skenario fiksi. Peneliti kemudian menerima dokumen tersebut melalui Telegram. Setelah memperoleh data, materi skenario dihafal dan kemudian diubah menjadi cerita video digital. ' Siswa diperkenalkan dengan teks fiksi dan ide-ide tata bahasa sebelum mengambil bagian dalam kegiatan mendongeng digital. Kemudian, situasi hipotetis disediakan untuk memperkuat informasi yang baru dipelajari. Penggunaan cerita digital FCM untuk mendidik dan mempelajari bahasa Inggris sebagai bahasa kedua pada akhirnya meningkatkan kemampuan berbicara siswa. Kata Kunci: Dongeng digital, Flipp classroom, Kemampuan berbicara.